Epidemiology of injuries and its impact among elderly: a descriptive community based cross-sectional study from central rural India - Gosavi, Shriram V.; Koparkar, Anil R.; Giri, Supriya A.; More, Komal D. (International Journal Of Community Medicine And Public Health, 2019)
Background: This study was to enlighten the prevalence, different types & impact of injuries in elderly population in rural area of middle income country (India). Methods: It was a community based descriptive cross-sectional study, conducted in all 24 villages under one Primary Health Centre of central India. The study was carried out from June 2009 to May 2011. Results: In the present study, prevalence of injury was 17.1%, which was highest among elderly ageing 65-69 years (36.8%) followed by elderly ageing 60-64 years (27.4%). Prevalence of injury was higher (20%) among males as compared to females (14%). Association of age, gender and injury was not statistically significant. Fall was the most common cause (34.7%) of injury followed by occupational (34.0%) and road traffic accidents (15.8%). Superficial injuries were the most common (32.6%) type of injuries followed by fracture (27.3%). Hospital admission required by 24.2% of elderly. We found 34.7% elderly was physically impaired and 26.3% physically disabled due to various injuries. Conclusions: In the present study we found injuries pose a major public health problem in elderly. Therefore there is a need of community based assessment on impact of injury among elderly in various parts of country to formulate appropriate health initiatives for prevention and optimum treatment of injuries in elderly.